Recent Advancement of Bio-inspired Nanomaterials and Its Antiurolithiatic Activity - F. Janeeta Priya; A. Leema Rose; S. Vidhya; A. Arputharaj (New Advances in Medicine and Medical Science Vol. 7, 2023)
This chapter reveals the characterization of struvite crystals and it prevents the growth of struvite crystals. Therefore the synthesis copper nanoparticles by using E. prostrata leaves act as a inhibitor for the formation of renal stone. Kidney stone disease is a crystal concretion formed usually within the kidneys. It is an increasing urological disorder of human health, affecting about 12% of the world population Organ dysfunction, especially kidney dysfunction, causes urinary tract infections that result in struvite urinary stones. The phytochemical qualitative analysis of E.prostrata leaves were done by utilizing standard procedure. UV-Visible spectroscopy shows SPR band at 256nm was used to validate the synthesis of copper nanoparticles. The FTIR spectral analyses of crystals with different percentage composition of synthesized copper nanoparticles are synthesized by E. prostrata leaves extract E.Prostrata mediated copper nanoparticles were crystallized and had a spherical shape, according to XRD and SEM. By using EDAX analysis the elemental signals were located. XRD analysis revealed crystalline nature of the synthesized copper nanoparticles. With an inhibitory efficiency of 88.3%, the copper nanoparticles mediated by E. Prostrata were found to be a potent inhibitor of the struvite crystals. The phytocomponents included in E. Prostrataleaves extract, which are responsible for its anti-urolithiatic activity, are confirmed by shifting of the band in FT-IR spectra.